Lyophilization process engineering and thermostability of ID93 + GLA-SE, a single-vial adjuvanted subunit tuberculosis vaccine candidate for use in clinical studies - Dutill, Timothy S.; Archer, Michelle C.; McCollum, Joseph; Press, Chris; McNeill, Lisa; Hawkins, Linda; Phan, Tony; Laursen, Erik D.; Cabullos, Richard; Bouchard, Lisa; Castro, Regie J.; Lin, Mong-Wu; et al. (Frontiers in Drug Delivery, 2022)
Promising clinical efficacy results have generated considerable enthusiasm for the potential impact of adjuvant-containing subunit tuberculosis vaccines. The development of a thermostable tuberculosis vaccine formulation could have significant benefits on both the cost and feasibility of global vaccine distribution. The tuberculosis vaccine candidate ID93 + GLA-SE has reached Phase 2 clinical testing, demonstrating safety and immunogenicity as a two-vial point-of-care mixture. Earlier publications have detailed efforts to develop a lead candidate single-vial lyophilized thermostable ID93 + GLA-SE vaccine formulation. The present report describes the lyophilization process development and scale-up of the lead candidate thermostable ID93 + GLA-SE composition. The manufacture of three full-scale engineering batches was followed by one batch made and released under current Good Manufacturing Practices (cGMP). Up to 4.5 years of stability data were collected. The cGMP lyophilized ID93 + GLA-SE passed all manufacturing release test criteria and maintained stability for at least 3 months when stored at 37°C and up to 24 months when stored at 5°C. This work represents the first advancement of a thermostable adjuvant-containing subunit tuberculosis vaccine to clinical testing readiness.